Implementation Port Security for Security Systems Network at the Computing Laboratory of Adisutjipto College of Technology - Sudaryanto, Sudaryanto (SENATIK STT Adisutjipto, 2018)
At the Computing Laboratory Adisutjipto College of Technology (STTA) there are switch devices and several personal computers connected directly to the server, so that the equipment in the laboratory can be used by students, employees and lecturers freely to explore the world without borders (internet) by utilizing the STTA bandwidth. The absence of a security system in the laboratory, users can use bandwidth without administrator permission to carry out activities that are not in accordance with the provisions of bandwidth usage in the STTA environment, thus disrupting Practical activities in the Laboratory. Many techniques can be done in minimizing the crime rate or the use of irresponsible users in this network, one technique that will be used to secure local networks is to use security ports on the switch. With port security implemented in the Laboratory STTA computing theft or excessive bandwidth usage can be reduced 70,19% and the use of Unshielded twisted-pair (UTP) cables with unregistered computer devices can be prevented.